Chapter New Frontiers in Reviewing: Experimental German Philosophical Review Practices around 1800 - Giesbers, Tom (Firenze University Press, 2025)
This paper introduces a grouping of experimental philosophical review journals around 1800, situated around editors associated with German idealism and German realism. By examining one journal edited by Reinhold the degree of experimentation is demonstrated within the context of experimental journals as well as established philosophical review standards in the second half of the 18th century. Among the transformations are the review length, scope, the use of mockery and literary style.